2011
DOI: 10.1177/147323001103900121
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Brain Response to Visual Sexual Stimuli is Different between Homosexual and Heterosexual Men

Abstract: The underlying neurobiological factors involved in sexual orientation are largely unknown. This study investigated whether neural circuits or different cognitive processes accounted for differences in brain activation in 14 heterosexual and 14 homosexual males. Brain scans were undertaken in each subject using functional magnetic resonance imaging while they viewed different sexual stimuli, i.e. heterosexual couple stimuli (HCS), gay couple stimuli (GCS), lesbian couple stimuli (LCS) and neutral stimuli (NS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Hand preference also appears to be related to other prenatally influenced variables, including the cognitive profile of the individual. In this respect, handedness, cognitive profile, gonadal hormones and sexual orientation all appear to be interrelated [8–11].…”
Section: Introductionmentioning
confidence: 97%
“…Hand preference also appears to be related to other prenatally influenced variables, including the cognitive profile of the individual. In this respect, handedness, cognitive profile, gonadal hormones and sexual orientation all appear to be interrelated [8–11].…”
Section: Introductionmentioning
confidence: 97%
“…The activated brain areas demonstrated by fMRI during sexual visual stimulation are the frontal lobe, cingulate gyrus, insula, corpus callosum, caudate nucleus, globus pallidus, inferior temporal lobes and thalamus. [6][7][8][9][10]13 Arnow et al 14 used fMRI to confirm the activated brain area during penile erection by visually evoked sexual stimulation, and reported that activation of the right insula and inferior portion of the insula, caudate nucleus, cingulate gyrus, posterior temporal lobe and hypothalamus is associated with penile tumescence. However, data addressing sexually aroused females are relatively limited.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of other fMRI studies of sexual arousal report activation of the amygdala, thalamus and hypothalamus in both men and women, although to different degrees. [6][7][8][9][10][11][12][13] Activation of the amygdala and hypothalamus are more prominent in men than in women when presented with the same sexual stimuli, even when women reported greater sexual arousal. 11,12 The amygdala and thalamus may have a greater role in mediating visual stimuli in male sexual behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations